Examining unsafe injection practices associated with auto-disable (AD) syringes: a systematic review. Issue 9 (2nd September 2021) - Ali Khan, Anokhi; Munir, Mehr; Miraj, Fatima; Imran, Shayan; Arif Siddiqi, Danya; Altaf, Arshad; Khan, Aamir Javed; Chandir, Subhash
ABSTRACT: Auto-disable (AD) syringes are specifically designed to prevent syringe reuse. However, the notion that specific AD syringe designs may be unsafe due to reuse concerns related to the syringe's activation point has surfaced. We conducted a systematic review for evidence on the association between AD syringe design and syringe reuse, adverse events following immunization (AEFI), or blood borne virus (BBV) transmission. We found no evidence of an association between AD syringe design and unsafe injection practices including syringe reuse, AEFIs, or BBVs. Authors of three records speculated about the possibility of AD syringe reuse through intentionally defeating the disabling mechanism, and one hinted at the possibility of reuse of larger-than-required syringes, but none reported any actual reuse instance. In contrast to AD syringes, standard disposable syringes continue to be reused; therefore, the global health community should expand the use of AD syringes in both immunization and therapeutic context as an essential strategy for curbing BBV transmission.